2016
DOI: 10.1038/ncomms13361
|View full text |Cite
|
Sign up to set email alerts
|

Social support reduces stress hormone levels in wild chimpanzees across stressful events and everyday affiliations

Abstract: Stress is a major cause of poor health and mortality in humans and other social mammals. Close social bonds buffer stress, however much of the underlying physiological mechanism remains unknown. Here, we test two key hypotheses: bond partner effects occur only during stress (social buffering) or generally throughout daily life (main effects). We assess urinary glucocorticoids (uGC) in wild chimpanzees, with or without their bond partners, after a natural stressor, resting or everyday affiliation. Chimpanzees i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
150
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 147 publications
(164 citation statements)
references
References 56 publications
4
150
2
1
Order By: Relevance
“…Results at the individual level of analysis indicate that perceived social support has a positive effect on stress. The results of the study support other studies that found a positive relationship between social support and stress (WITTIG et al 2016;GIBBONS 2010;STOK et al 2006). Likewise, in a study by STREET and colleagues (1999), individuals with large social networks are more likely to cope effectively with stressors.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Results at the individual level of analysis indicate that perceived social support has a positive effect on stress. The results of the study support other studies that found a positive relationship between social support and stress (WITTIG et al 2016;GIBBONS 2010;STOK et al 2006). Likewise, in a study by STREET and colleagues (1999), individuals with large social networks are more likely to cope effectively with stressors.…”
Section: Discussionsupporting
confidence: 80%
“…Social support is known to buffer disease-related distress and improve quality of life (ELLIOT 2008). Individuals who perceive high levels of social support feel less stress (WITTIG et al 2016;GIB-BONS 2010;STOK et al 2006). In a study, stress in parents has been shown to vary with social support (DUNN et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The formation and maintenance of social bonds has numerous links to fitness (e.g. offspring survival, longevity, siring of offspring, ability to respond to stressful events, rank acquisition) (Silk, Alberts, & Altmann, 2003;Schülke et al, 2010;Silk et al, 2010;Silk, Seyfarth, & Cheney, 2016;Wittig et al, 2016). Natural selection, then, might be expected to favour specific signals for coordinating distinct behaviours in the social domain as well.…”
Section: Signal Differentiationmentioning
confidence: 99%
“…Chimpanzees are an interesting species to study repeatability of urinary cortisol excretion and urinary cortisol reaction norms as infants are nursed by their mothers for around 4 years and carried and cared for even longer (Boesch and BoeschAchermann, 2000), rendering maternal priming of the HPA axis possible. Factors affecting glucocorticoid levels, such as circadian rhythms (Muller and Lipson, 2003), dominance rank (e.g., Muller and Wrangham, 2004;Anestis, 2005;Anestis et al, 2006;Muehlenbein and Watts, 2010), social dynamics (e.g., Fraser et al, 2008;Emery Thompson et al, 2010;Wittig et al, 2016), and maternal care (Murray et al, 2016) are well-studied in this species. This allows for an informed decision on potential control factors in statistical models and a sound biological interpretation of different patterns.…”
Section: Introductionmentioning
confidence: 99%